2022
DOI: 10.9734/ajmah/2022/v20i230432
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility Pattern in Otomycosis among Patients Attending a Tertiary Healthcare Institution in Port Harcourt, Nigeria

Abstract: Antifungal resistance is one of the factors considered to hamper effective treatment of otomycosis. Consequently, this study was aimed at isolating etiological agent for otomycosis among patients that visited University of Port Harcourt Teaching Hospital from June 2017 to June 2018 and carry out antifungal susceptibility testing with the isolates. Ear swab from 120 patients and 120 control group was aseptically collected. Nystatin, voriconazole and fluconazole were used for antifungal susceptibility testing by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…ketoconazole and fluconazole and amphotericin b had the poorest activity. This study is comparable with Sathiet al (2022) in Bangladesh showed 95% sensitive to voriconazole and 67% resistant to fluconazole and Oparaodu et al (2022) in Nigeria showed that highest sensitivity to voriconazole (76.9%) and highest resistance was to fluconazole (84.6%) and nystatin (53.9%) for yeast and highest sensitivity to voriconazole (66.7%) and 100% resistance to fluconazole for mold. 13,14 This study differ in resistant pattern with for mold showed nystatin (100%) resistant.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…ketoconazole and fluconazole and amphotericin b had the poorest activity. This study is comparable with Sathiet al (2022) in Bangladesh showed 95% sensitive to voriconazole and 67% resistant to fluconazole and Oparaodu et al (2022) in Nigeria showed that highest sensitivity to voriconazole (76.9%) and highest resistance was to fluconazole (84.6%) and nystatin (53.9%) for yeast and highest sensitivity to voriconazole (66.7%) and 100% resistance to fluconazole for mold. 13,14 This study differ in resistant pattern with for mold showed nystatin (100%) resistant.…”
Section: Resultssupporting
confidence: 89%
“…This study is comparable with Sathiet al (2022) in Bangladesh showed 95% sensitive to voriconazole and 67% resistant to fluconazole and Oparaodu et al (2022) in Nigeria showed that highest sensitivity to voriconazole (76.9%) and highest resistance was to fluconazole (84.6%) and nystatin (53.9%) for yeast and highest sensitivity to voriconazole (66.7%) and 100% resistance to fluconazole for mold. 13,14 This study differ in resistant pattern with for mold showed nystatin (100%) resistant. ketoconazole, fluconazole, amphotericin b showed highest resistance due to its low cost and its widespread availability in all levels of health care centers which in turns turned into increase drug resistance.…”
Section: Resultssupporting
confidence: 89%